Kajian in silico aktivitas antioksidan-antikanker senyawa fenolik dan flavonoid spesies mangifera menggunakan molecular docking PLANTs: Bahasa Indonesia - Hafiz Ramadhan; Dyera Forestryana; Putri Indah Sayakti; Mahmud Riyad; Ratna Restapaty (Universitas Islam Indonesia, 2023)
Background: The development of science and technology has created a study of anticancer drug discovery through molecular docking. This method can be applied to screening natural compounds that have antioxidant properties as anticancer candidates.Objective: The aim of the in-silico study is to find out the potential antioxidant-anticancer activities using molecular docking of phenolic and flavonoid compounds contained in the Mangifera species.Methods: Mangiferin, homomangiferin, isomangiferin, quercitrin, kaempferol 3-O-glucoside, catechin, epicatechin, daidzein, genistein, Î±-tocopherol, gallic acid as the test compounds and Vitamin C, doxorubicin, and hydroxyurea as comparison were prepared with MarvinSketch. The targeted protein data bank (PDB) codes used are 1V4S, 1XAN, 2BEL, 4K7O, 5M2F, 6COX, and 2W3L which were prepared with YASARA. The prepared compounds and proteins docked with each other using PLANTs software.Result: The in-silico results showed that only vitamin C can exceed the native ligand docking against the 1V4S receptor. Î±-tocopherol has a better binding affinity compared to vitamin C on 1XAN, 2BEL, and 5M2F but could not reach the native ligand score. All of the test compounds have potential antioxidant activity against the 4K7O protein receptor, but Î±-tocopherol is the only one that has the ability to inhibit the 6COX protein receptor. Î±-tocopherol also has better anticancer activity against breast cancer initiator (2W3L) compared to other test compounds, doxorubicin, hydroxyurea, and native ligands. Conclusion: The conclusion is that Î±-tocopherol has the most potential as an antioxidant and anticancer candidate through in silico studies.